Examination of the Trait Anxiety Levels among Male Basketball Players in the Ages from 13 to 15 in View of Various Variables - Ahmet Uzun; Atilla Pulur; Ebru Karabulut; Kaan Eroğlu (Türk Spor ve Egzersiz Dergisi, 2014)
What was intended with this study was to ascertain the Trait Anxiety levels of national team-nominee male basketball players between the ages of 13-15, and to investigate the differences thereof in view of personal variables. The study was participated by the whole of 102 national team-nominee sportspersons, having been selected from 81 cities, with an age average of 13.84 ± 0.592, and with a sports age average of 5.12± 1.80. As being the data collection tools, alongside the “Personal Information Form”, the “Trait Anxiety Scale”, which has been developed by Spielberg et al., and been adapted to Turkish by Öner amp; Le Compte, was used in the study. While the t-test and Single Direction Variance Analyses (ANOVA) were used in the analysis of the data, upon taking the percentage and frequency values, Krusukal Wallis Test was further used for non-parametric values, and the  relevance at p lt;0.05 level was sought. From the findings of the research, the trait anxieties were found out to be high. Besides, a meaningful relevance between the variables of family income, educational levels of the parents, and school type with the trait anxieties was further ascertained. On the other hand, no meaningful relevance was found out between the variables of age, sports year, and the positions in play with the trait anxiety scores.